Cathelicidin LL-37-induced transcriptome of human keratinocyte identifies chemokine CXCL10 link to T cell-mediated rosacea pathogenesis via JAK-1/STAT-1 pathway - Abdul W. Ansari (14557391) (2025)
Rosacea is a chronic inflammatory disease of facial skin with unknown pathophysiology. Abnormal overexpression of human antimicrobial peptide LL-37 is a hallmark of rosacea. However, its significance in the rosacea pathogenesis is not fully understood. We sought to understand the molecular mechanisms of LL-37-mediated rosacea-like inflammation in an in-vitro model of normal human epidermal keratinocytes. Transcriptome profiling of LL-37-treated keratinocytes identified signatures of interferon (IFN)-stimulating genes (ISGs) such as CXCL10, IFIT2, RSAD2 and CXCL11 among the top upregulated differentially expressed genes. Gene ontogeny (GO) enrichment of biological processes revealed activation of cellular response to molecules of bacterial origin, response to chemokines, and cytokine mediated signaling pathways. While KEGG enrichment analysis revealed the activation of TNF signaling, IL-17 signaling, NF-kB signaling and chemokine signaling among the most significant pathways. Remarkably, T cell recruiting chemokine CXCL10 turns out to be the most abundant inflammatory mediator overexpressed upon LL-37 exposure. Mechanistically, LL-37 induced CXCL10 production relied on JAK-1/STAT-1 signaling pathway. In summary, our findings provide a crucial link to keratinocyte: T cell crosstalk and blockade of CXCL10:CXCR3 axis or JAK-1/STAT-1 pathways can be an effective anti-inflammatory strategy to reduce rosacea inflammation by restricting pathogenic T cells infiltration. Other Information Published in: Journal of Investigative Dermatology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jid.2025.08.003